Implementasi Penilaian Non-Tes Berbasis Akhlak pada Pembelajaran PAI di Kelas 11 SMK Muhammadiyah 4 Surakarta - Ahmad Fathun Qoriib; Azzmi Sholahudin; Ilham Ahmad Rifai; Muh. Iqbal Zaini; Nurul Latifatul Inayati (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
This article aims to examine the implementation of morals-based non-test assessment in PAI learning in grade 11 of SMK Muhammadiyah 4 Surakarta, focusing on its influence on students' character development. Islamic Religious Education (PAI) has an important role in instilling moral values. In this context, morals-based non-test assessment is an effective approach to assessing students' character development, as it focuses on observing their behavior and attitudes. At SMK Muhammadiyah 4 Surakarta, the implementation of this method is expected to help students not only understand religious teachings in theory, but also apply them in daily life. This research is a type of field research that is descriptive qualitative in nature. The main focus of this research is to understand the concept of evaluation in Islamic Religious Education (PAI) learning, which includes both test-based and non-test evaluation methods at SMK Muhammadiyah 4 Surakarta. In this study, a phenomenological approach is used to explore the experiences and understanding of individuals or groups regarding the phenomenon under investigation. Moral-based non-test assessment in PAI learning aims to evaluate students' moral values in everyday life. In contrast to test assessments that measure cognitive abilities. The implementation of morals-based non-test assessment faces obstacles such as difficulties in measuring morals objectively and limited time for observation.Morals-based non-test assessment in Islamic Religious Education (PAI) learning at SMK Muhammadiyah 4 Surakarta has an important role in shaping student character, in addition to mastery of academic material.